2021
DOI: 10.1053/j.gastro.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fecal Biomarkers That Precede Clinical Diagnosis of Ulcerative Colitis

Abstract: Healthy 1 st degree IBD relatives Pre-UC Post-UC Matched HC Follow-up Proteolytic activity Microbiotahumanized mice Proteolytic activity Low-grade colonic inflammation Fecal proteolytic activity as early biomarker Microbiota composition BACKGROUND & AIMS: Altered gut microbiota composition and function have been associated with inflammatory bowel diseases, including ulcerative colitis (UC), but the causality and mechanisms remain unknown. METHODS: We applied 16S ribosomal RNA gene sequencing, shotgun metagenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
89
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 49 publications
8
89
0
5
Order By: Relevance
“…Alternatively, the documented genetic and/ or microbial-independent environmental factors associated with IBD may promote inflammation and oxidative stress, which subsequently results in a shift in microbial composition. A recent study has shown that increased fecal proteolytic activity and microbiota changes precede diagnoses of ulcerative colitis (30). In addition, the altered humoral and cellular acquired immune responses towards bacterial antigens that characterize IBD, particularly Crohn's disease (31), may predate disease onset (32).…”
Section: Role Of Intestinal Microbiota In Autoimmune Diseases Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Alternatively, the documented genetic and/ or microbial-independent environmental factors associated with IBD may promote inflammation and oxidative stress, which subsequently results in a shift in microbial composition. A recent study has shown that increased fecal proteolytic activity and microbiota changes precede diagnoses of ulcerative colitis (30). In addition, the altered humoral and cellular acquired immune responses towards bacterial antigens that characterize IBD, particularly Crohn's disease (31), may predate disease onset (32).…”
Section: Role Of Intestinal Microbiota In Autoimmune Diseases Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Moreover, the study illustrated an increased level of elastase activity in Bacteroides, isolated from fecal samples. Consequently, the study opened different pathways for early investigation of predisposed people to UC and also for possible treatments by reduction of high proteolytic activity [24].…”
Section: Fecal Analysismentioning
confidence: 99%
“…6 In a recent study, we demonstrated that increased fecal proteolytic activity precedes the clinical diagnosis of ulcerative colitis and associates with gut microbiota changes that are proinflammatory. 7 Future studies will be needed to investigate common environmental and genetic factors involved in the association of these disorders, among others IBD, CeD, type 1 diabetes, and PSC.…”
mentioning
confidence: 99%